Loss of Bcl-G, a Bcl-2 family member, augments the development of inflammation-associated colorectal cancer - Nguyen, Paul M. (Cell Death Differ, 2019)
Gastrointestinal epithelial cells provide a selective barrier that segregates the host immune system from luminal microorganisms, thereby contributing directly to the regulation of homeostasis. We have shown that from early embryonic development Bcl-G, a Bcl-2 protein family member with unknown function, was highly expressed in gastrointestinal epithelial cells. While Bcl-G was dispensable for normal growth and development in mice, the loss of Bcl-G resulted in accelerated progression of colitis-associated cancer. A label-free quantitative proteomics approach revealed that Bcl-G may contribute to the stability of a mucin network, which when disrupted, is linked to colon tumorigenesis. Consistent with this, we observed a significant reduction in Bcl-G expression in human colorectal tumors. Our study identifies an unappreciated role for Bcl-G in colon cancer.